The Implementation of SQ3R Method to Develop Students’ Reading Skill on Islamic Texts in EFL Class in Indonesia - Abdul Gafur Marzuki (Register Journal, 2019)
The study aims at analyzing the development of students’ reading skill on Islamic texts in EFL class in Indonesia through SQ3R method. The research was designed as a collaborative classroom action research which was carried out at TBI-4 FTIK IAIN Palu. The subject of the research was the third semester students of TBI-4 FTIK IAIN Palu consisting of 24 students. The research was conducted in one cycle through stages of planning, acting, observing and reflecting. The cycle consists of three meetings. The researcher with his collaborator collected the data by using observation checklists, field notes, camera recording, and test. The result showed that the SQ3R method could develop students’ reading skill. This fact was supported by the result of achievement test. There were 19 students (75%) who got score greater than 80 of 24 students, there were 6 students who could not reach the score. The research was stopped after the third meeting of cycle 1 in which the result of students’ achievement test have met the criteria of success. Based on this finding, the researcher concluded that the implementation of SQ3R method in teaching and learning process can develop students’ reading skill on Islamic texts.Keywords: Implementation, Reading Skill, SQ3R method.